2017
DOI: 10.1080/02688697.2017.1339227
|View full text |Cite
|
Sign up to set email alerts
|

Encephaloduroateriosynangiosis (EDAS) in the management of Moyamoya syndrome in children with sickle cell disease

Abstract: EDAS is a well-tolerated revascularisation procedure for children with MMS. The prevention of further infarcts in our group with sickle cell disease has allowed these children to resume normal school activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…183 Down syndrome (with a 26-fold increased likelihood of moyamoya), neurofibromatosis type I (with ≈2%-5% prevalence of moyamoya), SCD, and other associated conditions are summarized in Table 2. 177,181,[184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199] If moyamoya is identified on MRI, then DSA should be strongly considered because this modality has increased diagnostic sensitivity for moyamoya compared with MRI (including the ability to better differentiate vasculitis) and offers important data germane to preoperative planning. Specifically, transdural collaterals visualized on DSA are critical biomarkers of disease that can assess angiogenic potential (particularly in combination with proteomic assays), that can predict 1-year radiographic outcomes from surgery, and, when incorporated into surgical planning, have been demonstrated to reduce…”
Section: Intracranial Arteriopathymentioning
confidence: 99%
“…183 Down syndrome (with a 26-fold increased likelihood of moyamoya), neurofibromatosis type I (with ≈2%-5% prevalence of moyamoya), SCD, and other associated conditions are summarized in Table 2. 177,181,[184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199] If moyamoya is identified on MRI, then DSA should be strongly considered because this modality has increased diagnostic sensitivity for moyamoya compared with MRI (including the ability to better differentiate vasculitis) and offers important data germane to preoperative planning. Specifically, transdural collaterals visualized on DSA are critical biomarkers of disease that can assess angiogenic potential (particularly in combination with proteomic assays), that can predict 1-year radiographic outcomes from surgery, and, when incorporated into surgical planning, have been demonstrated to reduce…”
Section: Intracranial Arteriopathymentioning
confidence: 99%
“…Risk of MA disease has been also attributed to mutations in GUCY1A3 gene, encoding the major nitric oxide receptor in vascular smooth muscle cells (vSMCs) in achalasia cases [ 11 ]. Other sporadic syndromic cases of MA have been reported, as resumed in Table 1 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, these observations are not able to fully explain the pathogenesis of MA, which is believed to be much more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the unilateral MMD might be a suitable model to examine the pathogenetic process of MMD, because the bilateral MMD exhibits complex and ambiguous pathological findings that do not allow identification of cause versus effect [ 18 ]. In order to accurately analyze the progression of the unilateral MMD, MMS was excluded in our study because the MMS-associated diseases such as sickle cell disease, Graves’ disease (GD), and Down syndrome [ 1 , 5 ] might have positive or negative effects on the angiographic and symptomatic progression. For example, Chen et al [ 5 ] observed that the disease progression was more frequent in MMS patients with GD than that in patients without GD during the follow-up period, especially in unilateral disease.…”
Section: Discussionmentioning
confidence: 99%